Mass transfer performance of rotating packed beds with blade packings in absorption of CO2 into MEA solution. (June 2016) - Lin, Chia-Chang; Kuo, Yi-Wen
Highlights: CO2 absorption was performed in RPB with blade packings by MEA solution. Rotational speed positively affected KG a values in RPB with blade packings. KG a values increased with an increasing inner radius of the bed and a decreasing outer radius of the bed. KG a values increased with gas flow rate and liquid flow rate. RPB with blade packings has great potential in CO2 removal from exhaust gases by MEA solution. Abstract: This study investigates the mass transfer achieved using the rotating packed bed (RPB) with blade packings in the absorption of carbon dioxide (CO2 ) using monoethanolamine (MEA) solution. The overall volumetric gas-phase mass transfer coefficients (KG a) were evaluated using 1 vol% CO2 and 1 mol/L MEA solution in three RPBs with blade packings and the effects of rotational speed, gas flow rate, and liquid flow rate thereon were determined. The rotational speed positively influenced the KG a values for all RPBs. The obtained results revealed that the KG a values increased as the inner radius of the bed was increased, the outer radius of the bed was decreased, the liquid flow rate was increased or the gas flow rate was increased. The KG a values obtained using an MEA solution exceeded those obtained using an NaOH solution. The RPB with blade packings is a more effective gas–liquid contactor than one with structured packings in the absorption of CO2 using MEA solution.